Impact of conservation tillage and organic farming on the diversity of arbuscular mycorrhizal fungi. (May 2015) - Säle, Verena; Aguilera, Paula; Laczko, Endre; Mäder, Paul; Berner, Alfred; Zihlmann, Urs; van der Heijden, Marcel G.A.; Oehl, Fritz
Abstract: Communities of arbuscular mycorrhizal fungi (AMF) are strongly affected by land use intensity and soil type. The impact of tillage practices on AMF communities is still poorly understood, especially in organic farming systems. Our objective was to investigate the impact of soil cultivation on AMF communities in organically managed clay soils of a long-term field experiment located in the Sissle valley (Frick, Switzerland) where two different tillage (reduced and conventional mouldboard plough tillage) and two different types of fertilization (farmyard manure & slurry, or slurry only) have been applied since 2002. In addition, a permanent grassland and two conventionally managed croplands situated in the neighborhood of the experiment were analyzed as controls. Four different soil depths were studied including top-soils (0–10 and 10–20 cm) of different cultivation regimes and undisturbed sub-soils (20–30 and 30–40 cm). The fungi were directly isolated from field soil samples, and additionally spores were periodically collected from long-term trap culture (microcosm) systems. In total, >50, 000 AMF spores were identified on the species level, and 53 AMF species were found, with 38 species in the permanent grassland, 33 each in the two reduced till organic farming systems, 28–33 in the regularly plowed organic farming systems, and 28–33 in the non-organic conventional farming systems. AMF spore density and species richness increased in the top-soils under reduced tillage as compared to the ploughed plots. In 10–20 cm also the Shannon–Weaver AMF diversity index was higher under reduced tillage than in the ploughed plots. Our study demonstrates that AMF communities in clay soils were affected by land use type, farming system, tillage as well as fertilization strategy and varying with soil depth. Several AMF indicator species especially for different land use types and tillage strategies were identified from the large data set. Highlights: AM fungi were studied in organic farming under reduced tillage in top- and sub-soils. >50, 000 AMF spores and 53 species were identified. AMF spore density, species richness and diversity were increased in reduced till. AMF communities were affected by land use type, tillage and fertilization strategy. AMF indicator species could be deduced from the large data set obtained.